Unique tertiary and neighbor interactions determine conservation patterns of Cis Watson-Crick A/G base-pairs - Sponer, Jirí; Mokdad, Ali; Sponer, Judit E; Spacková, Nad'a; Leszczynski, Jerzy; Leontis, Neocles B (Journal of molecular biology, 2003)
X-ray, phylogenetic and quantum chemical analysis of molecular interactions and conservation patterns of cis Watson-Crick (W.C.) A/G base-pairs in 16S rRNA, 23S rRNA and other molecules was carried out. In these base-pairs, the A and G nucleotides interact with their W.C. edges with glycosidic bonds oriented cis relative to each other. The base-pair is stabilised by two hydrogen bonds, the C1'-C1' distance is enlarged and the G(N2) amino group is left unpaired. Quantum chemical calculations show that, in the absence of other interactions, the unpaired amino group is substantially non-planar due to its partial sp(3) pyramidalization, while the whole base-pair is internally propeller twisted and very flexible. The unique molecular properties of the cis W.C. A/G base-pairs make them distinct from other base-pairs. They occur mostly at the ends of canonical helices, where they serve as interfaces between the helix and other motifs. The cis W.C. A/G base-pairs play crucial roles in natural RNA structures with salient sequence conservation patterns. The key contribution to conservation is provided by the unpaired G(N2) amino group that is involved in a wide range of tertiary and neighbor contacts in the crystal structures. Many of them are oriented out of the plane of the guanine base and utilize the partial sp(3) pyramidalization of the G(N2). There is a lack of A/G to G/A covariation, which, except for the G(N2) position, would be entirely isosteric. On the contrary, there is a rather frequent occurrence of G/A to G/U covariation, as the G/U wobble base-pair has an unpaired amino group in the same position as the cis W.C. G/A base-pair. The cis W.C. A/G base-pairs are not conserved when there is no tertiary or neighbor interaction. Obtaining the proper picture of the interactions and phylogenetic patterns of the cis W.C. A/G base-pairs requires a detailed analysis of the relation between the molecular structures and the energetics of interactions at a level of single H-bonds and contacts.
Keywords: vodíková vazba; RNA transferová; konformace nukleové kyseliny; RNA, Ribosomal, 16S; Dimerization; Nucleic Acid Conformation; Databases as Topic; DNA, Bacterial; Protein Binding; ribozomy; DNA; krystalografie rentgenová; RNA, Ribosomal, 23S; dimerizace; HIV-1; RNA, Viral; databáze jako téma; Hydrogen Bonding; RNA, Transfer; RNA; DNA bakterií; Crystallography, X-Ray; párování bází; chemické modely; RNA ribozomální 16S; RNA katalytická; fylogeneze; RNA ribozomální 23S; vazba proteinů; RNA, Catalytic; Base Pairing; Signal Recognition Particle; Models, Chemical; Phylogeny; signál-rozpoznávající částice; RNA virová; Ribosomes